Context‐dependent effects of Y chromosome and mitochondrial haplotype on male locomotive activity in Drosophila melanogaster. (12th August 2015) - Dean, R.; Lemos, B.; Dowling, D. K.
Abstract Some regions of the genome exhibit sexual asymmetries in inheritance and are thus subjected to sex‐biased evolutionary forces. Maternal inheritance of mitochondrial DNA (mtDNA) enables mtDNA mutations harmful to males, but not females, to accumulate. In the face of male‐harmful mtDNA mutation accumulation, selection will favour the evolution of compensatory modifiers in the nuclear genome that offset fitness losses to males. The Y chromosome is a candidate to host these modifiers, because it is paternally inherited, known to harbour an abundance of genetic variation for male fertility, and therefore likely to be under strong selection to uphold male viability. Here, we test for intergenomic interactions involving mtDNA and Y chromosomes in male Drosophila melanogaster. Specifically, we examine effects of each of these genomic regions, and their interaction, on locomotive activity, across different environmental contexts – both dietary and social. We found that both the mtDNA haplotype and Y chromosome haplotype affected activity in males assayed in an environment perceived as social. These effects, however, were not evident in males assayed in perceived solitary environments, and neither social nor solitary treatments revealed evidence for intergenomic interactions. Finally, the magnitude and direction of these genetic effects was further contingent on the diet treatment of the males. Thus, genes within the mtDNA and Y chromosome are involved in genotype‐by‐environment interactions. These interactions might contribute to the maintenance of genetic variation within these asymmetrically inherited gene regions and complicate the dynamics of genetic interactions between the mtDNA and the Y chromosome.